ChemInform Abstract: C—H Activation/Functionalization Catalyzed by Simple, Well‐Defined Low‐Valent Cobalt Complexes. Issue 29 (July 2015) - Fallon, Brendan J.; Derat, Etienne; Amatore, Muriel; Aubert, Corinne; Chemla, Fabrice; Ferreira, Franck; Perez‐Luna, Alejandro; Petit, Marc
Abstract An optimized method is developed which demonstrates the utility of low‐valent Co‐phosphine catalyst to allow the direct C—H alkenylation of aromatic imines using internal alkynes as coupling partners.